Kontribusi Prof. Dr. K.H. Sahabuddin dalam Pengembangan Pendidikan Islam di Sulawesi Barat: Suatu Kajian Sejarah Pendidikan - Zulmaizar, Muhammad Muzani; Afif, Muh. Bahrul; Wahyudhi, Johan (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Education in West Sulawesi faces significant challenges, particularly in access and quality, despite efforts to improve it. Prof. Dr. K.H. Sahabuddin emerged as an important figure in the development of Islamic education in this area, through the establishment of Al Assariah University of Mandar (UNASMAN). This research aims to explore the idea of Islamic education developed by K.H. Sahabuddin, as well as its impact on the people of West Sulawesi, focusing on the integration of religious values and modern education. This research used a qualitative approach with a case study method. Data were collected through in-depth interviews with educational figures, santri, and people involved in the educational institutions established by K.H. Sahabuddin. Document analysis was also conducted on related works and literature to understand his ideas and contributions. The results show that K.H. Sahabuddin succeeded in creating an educational approach that integrates spiritual and intellectual aspects, known as “rasa education.” This approach not only enriches spiritual understanding, but also enriches the students' understanding of spirituality. This approach not only enriched students' spiritual understanding, but also encouraged them to adopt a modern and critical mindset. His contribution to education has provided encouragement for the Mandarese people to pursue higher education and improve their quality of life.